Towards an analysis of voting power in parliament: an exploration into coalition-making in Nordic parliaments - Lane, Jan-Erik; Maeland, Reinert (Acta Politica, 2007)
In this explorative paper, coalitions in national assemblies are analysed as n-person games with the Penrose-Banzhaf solution concept. It is shown that forming minority coalitions may result from a rational strategy to maximize voting power. Thus, there is no need to attempt a permanent minimum winning coalition. Moreover, maximizing voting power for a group of players like a disciplined political party involves the making of temporary coalitions over the entire political space, as anything goes. The examples looked at include the present Nordic parliamentary situation in Denmark, Finland, Sweden, Norway and Iceland.